A PMMA microsphere lithium ion battery separator and a battery using the same
By etching the PMMA microspheres and combining them with dispersants and adhesives, a high-adhesion strength PMMA microsphere coating is formed, which solves the problem of insufficient bonding strength of the existing PMMA microsphere lithium-ion battery separator, and significantly improves the Electrochemical properties of lithium-ion batteries.
Patent Information
- Application Number
- CN202411558225.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-04
AI Technical Summary
The adhesive strength of the existing PMMA microsphere lithium-ion battery separator is low, affecting the electrochemical performance of lithium-ion batteries.
By etching the PMMA microspheres, their porosity is increased and combined with dispersant and adhesive, a high bonding strength PMMA microsphere coating is formed.
Improves the electrochemical performance of lithium-ion batteries, including better electrolyte flow and liquid retention channels, enhanced ion conductivity, improved cell rate performance and cycling performance.
Smart Images

Figure CN119050603B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to a PMMA microsphere lithium ion battery separator and a battery using the same. Background Art
[0002] As a clean and renewable energy source, lithium-ion batteries are widely used in consumer electronics, transportation and other fields due to their high energy density, long cycle life and environmental friendliness. Lithium-ion batteries are generally composed of four parts: positive electrode, negative electrode, diaphragm and electrolyte solution. Among them, the diaphragm is called the "third electrode" in lithium-ion batteries and plays an important role in isolating positive and negative electrodes, transmitting lithium ions and isolating electrons. The performance of the diaphragm determines the interface structure and internal resistance of the battery, and directly affects the capacity, cycle and safety performance of the battery. A diaphragm with excellent performance plays an important role in improving the comprehensive performance of the battery.
[0003] In the early stage of lithium-ion battery development, polyolefin microporous membranes were widely used due to their excellent mechanical properties, chemical stability, wide sources of raw materials, and low manufacturing costs. However, due to the low melting point of polyolefin materials, single-layer polyethylene and polypropylene have poor high temperature resistance. When overheating occurs inside the battery, the polyolefin separator is prone to shrinkage or damage, which leads to battery failure and even thermal runaway, resulting in safety accidents.
[0004] To solve this problem, commonly used methods include coating one or both sides of the polyolefin separator with ceramic slurry to form a heat-resistant ceramic layer with a thickness of 2-5μm, designing a thermal closure mechanism for a multi-layer polyolefin composite structure, etc. However, the ceramic particles have a large specific gravity, and the presence of the ceramic heat-resistant layer will additionally increase the mass and thickness of the composite separator, which is not conducive to the improvement of the energy density of lithium-ion batteries. The thickness of the multi-layer polyolefin composite isolation membrane is usually above 25μm, which is not conducive to the rapid penetration of the electrolyte and reduces the volume energy density of the lithium-ion battery. Its use is subject to certain restrictions.
[0005] In addition, most diaphragms are generally coated with a layer of polyvinylidene fluoride (PVDF) adhesive after the ceramic coating on the surface. The adhesive force is relatively small, resulting in low liquid absorption rate of the diaphragm, low lithium ion conduction efficiency, and affecting battery life. At the same time, PVDF is a fluorine-containing material, which is easy to pollute the environment during the production process, is expensive, and has a high swelling rate. Based on this, the industry has begun to develop materials to replace PVDF. Other fluorine-free polymer microspheres represented by PMMA (polymethyl methacrylate) have become a better choice because of their low cost, mature large-scale production, and good bonding effect.
[0006] Chinese patent CN114361706A "A coated diaphragm and its preparation method" discloses a lithium-ion battery diaphragm including porous PMMA microspheres, ceramic particles, a thickener, an aqueous adhesive and a wetting agent. The porous polymer PMMA provides a better flow and liquid retention channel for the electrolyte, thereby improving the wettability of the diaphragm with the electrolyte. However, the ceramic particles in the coated diaphragm account for a high proportion, the density of the particles is large, the particle size is not easy to control, and the porosity of the porous PMMA microspheres is not high, and the bonding strength is low. The impact on the electrochemical performance of lithium-ion batteries still needs to be further improved.
[0007] Therefore, it is of great significance to develop a PMMA microsphere lithium ion battery separator with high bonding strength that can effectively improve the electrochemical performance of lithium ion batteries, as well as a preparation method and application thereof. Summary of the invention
[0008] In view of the fact that the existing PMMA microsphere lithium ion battery separator has low bonding strength of PMMA microspheres and the influence on the electrochemical performance of lithium ion batteries still needs to be further improved, the present invention provides a PMMA microsphere lithium ion battery separator and a battery using the same. By etching the PMMA microspheres, the porosity of the PMMA microspheres can be effectively increased, and the electrochemical performance of the lithium ion battery can be effectively improved. The PMMA microsphere lithium ion battery separator can effectively reduce the mass and thickness of the lithium ion battery separator, provide a better circulation and liquid retention channel for the electrolyte, improve the wettability of the separator and the electrolyte, improve its ionic conductivity, improve the rate performance and cycle performance of the battery cell, have high bonding strength, are not easy to fall off, are simple in preparation method, and have good economic and environmental benefits.
[0009] To achieve the above object, the technical solution adopted by the present invention is:
[0010] A PMMA microsphere lithium-ion battery separator, comprising: a base film, and a PMMA microsphere coating disposed on at least one side of the base film, wherein the PMMA microsphere coating comprises at least etched PMMA microspheres, a dispersant, and an adhesive;
[0011] The etched PMMA microspheres are prepared by the following preparation method:
[0012] S1. PMMA and PVP are mixed, melt-blended at 130-140°C, and atomized and granulated at 80-100°C to obtain polymer microspheres;
[0013] S2. The polymer microspheres obtained in S1 are placed in deionized water, etched, centrifuged, washed with deionized water for 3-5 times, and dried to obtain the etched PMMA microspheres.
[0014] Furthermore, the mass ratio of PMMA to PVP in S1 is 1:(1-3).
[0015] Furthermore, the etching process in S2 is to remove PVP by stirring at a constant speed for 6-8 hours.
[0016] Furthermore, the average particle size of the etched PMMA microspheres is 100-300 nm.
[0017] Furthermore, the single-side thickness of the PMMA microsphere coating is 2-5 μm.
[0018] Furthermore, the base film material is one or more of PE, PP, PI, PEI, and PET.
[0019] Furthermore, the base film has a thickness of 5-15 μm.
[0020] Furthermore, the dispersant is one or more of polyvinyl alcohol, carboxymethyl cellulose and its salts, polyvinyl pyrrolidone, and polyacrylamide.
[0021] Furthermore, the adhesive is one or more of polymethacrylic acid, polymethyl methacrylate, styrene-butadiene rubber, polyurethane, and epoxy resin.
[0022] Another object of the present invention is to provide a lithium ion battery using the PMMA microsphere lithium ion battery separator.
[0023] A lithium-ion battery, characterized in that it comprises a positive electrode, a negative electrode, an electrolyte located between the positive electrode and the negative electrode, and a PMMA microsphere lithium-ion battery separator as described in any one of the above items.
[0024] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0025] The present application prepares a PMMA microsphere lithium-ion battery separator by compounding a base film and a PMMA microsphere coating including etched PMMA microspheres, a dispersant, and an adhesive. The PMMA microspheres are subjected to a series of treatments such as melt blending, atomization granulation, and etching treatment to obtain nano-sized large-porosity etched PMMA microspheres, which effectively reduce the mass and thickness of the lithium-ion battery separator, provide a better circulation and liquid retention channel for the electrolyte, improve the wettability of the separator and the electrolyte, improve its ionic conductivity, improve the rate performance and cycle performance of the battery cell, and thus enhance the charge and discharge performance of the lithium-ion battery. At the same time, the molecular structure of the etched PMMA microspheres, dispersants and adhesives contains a large number of polar groups, with strong intermolecular forces, high bonding strength, and is not easy to fall off, which can improve the lithium ion conduction efficiency and thus extend the service life of lithium ion batteries. Batteries using the PMMA microsphere lithium ion battery separator have high charge and discharge specific capacity and excellent cycle stability. The preparation method of the PMMA microsphere lithium ion battery separator is simple and easy to operate. Compared with the currently widely used PVDF, the raw materials have a wide source, low production cost, no pollution to the environment, and good economic and environmental benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The invention is further described using the accompanying drawings, but the embodiments in the accompanying drawings do not constitute any limitation to the invention. A person skilled in the art can obtain other drawings based on the following drawings without creative work.
[0027] Figure 1 This is the microstructure diagram of the PMMA microspheres of the PMMA microsphere lithium-ion battery separator of this application. DETAILED DESCRIPTION
[0028] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention is further described by the following examples. Obviously, the following examples are only part of the embodiments of the present invention, rather than all the embodiments; it should be understood that the embodiments of the present invention are only used to illustrate the technical effects of the present invention, rather than to limit the scope of protection of the present invention.
[0029] The present invention will be specifically described below by examples, and these examples are not intended to limit the present invention in any way. It will be appreciated by those skilled in the art that these examples are only intended to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods for the unrecorded specific conditions in the following examples are usually performed under normal conditions or according to the conditions recommended by the manufacturer. Unless otherwise indicated, percentages and parts are calculated by weight. The following examples are mainly for a better understanding of the analytical method of the present invention and do not exhaust all operating modes. Parts by weight hereinafter may represent conventional unit measurements in the art, such as kilograms, grams, etc., or may represent ratios between the components, such as mass or weight ratios, etc.
[0030] The raw materials in the examples can all be obtained commercially; unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0031] Embodiment 1: A method for preparing a PMMA microsphere lithium ion battery separator, comprising the following steps:
[0032] S1. 1 part by mass of PMMA and 3 parts by mass of PVP were mixed, melt-blended at 130°C, atomized and granulated at 100°C, the spray chamber gradient temperature was set to 100°C, the atomization pressure was 0.5MPa, a plurality of atomizing nozzles were provided on the atomizing disk, the nozzle inner diameter was 0.5mm, the peristaltic pump feed rate was 1L / h, the air volume was 72CFM, the material stayed for 3s, the powder was settled in a collection bottle, and the polymer microspheres were obtained after cooling;
[0033] S2. The polymer microspheres obtained in S1 are placed in deionized water, etched, stirred at a constant speed for 7 hours to remove PVP, centrifuged, washed with deionized water for 3-5 times, and dried to obtain the etched PMMA microspheres with an average particle size of 100-300 nm.
[0034] 10 parts by mass of the etched PMMA microspheres prepared above, 2 parts by mass of dispersant polyvinyl alcohol, and 7 parts by mass of adhesive polymethyl methacrylate were added to an appropriate amount of deionized water, and dispersed at a stirring speed of 1000 rpm for 30 minutes. The resulting mixed solution was placed in a ball mill and ball milled at 600 rpm for 1 hour to prepare a mixture slurry; the mixture slurry was coated on both sides of a 10 μm PE base film to form a PMMA microsphere coating with a single-side thickness of 3 μm, and then placed in an oven at 60°C for drying to obtain the PMMA microsphere lithium-ion battery separator.
[0035] Embodiment 2: A method for preparing a PMMA microsphere lithium ion battery separator, comprising the following steps:
[0036] S1. 1 part by mass of PMMA and 1 part by mass of PVP were mixed, melt-blended at 140°C, atomized and granulated at 80°C, the spray chamber gradient temperature was set to 80°C, the atomization pressure was 0.5MPa, a plurality of atomizing nozzles were provided on the atomizing disk, the inner diameter of the nozzle was 0.5mm, the peristaltic pump feed rate was 1L / h, the air volume was 72CFM, the material stayed for 3s, the powder was settled in the collection bottle, and the polymer microspheres were obtained after cooling;
[0037] S2. The polymer microspheres obtained in S1 are placed in deionized water, etched, stirred at a constant speed for 8 hours to remove PVP, centrifuged, washed with deionized water for 3-5 times, and dried to obtain the etched PMMA microspheres with an average particle size of 100-300 nm.
[0038] 10 parts by mass of the etched PMMA microspheres prepared above, 2 parts by mass of dispersant sodium carboxymethyl cellulose, and 7 parts by mass of adhesive polymethacrylic acid were added to an appropriate amount of deionized water, and dispersed at a stirring speed of 1000 rpm for 30 minutes. The resulting mixed solution was placed in a ball mill and ball milled at 600 rpm for 1 hour to prepare a mixture slurry; the mixture slurry was coated on both sides of a 10 μm PE / PP composite base film to form a PMMA microsphere coating with a single-side thickness of 3 μm, and then placed in an oven for drying at 60°C to obtain the PMMA microsphere lithium-ion battery separator.
[0039] Embodiment 3: A method for preparing a PMMA microsphere lithium ion battery separator, comprising the following steps:
[0040] S1. 1 part by mass of PMMA and 2 parts by mass of PVP were mixed, melt-blended at 135°C, atomized and granulated at 120°C, the spray chamber gradient temperature was set to 120°C, the atomization pressure was 0.5MPa, a plurality of atomizing nozzles were provided on the atomizing disk, the nozzle inner diameter was 0.5mm, the peristaltic pump feed rate was 1L / h, the air volume was 72CFM, the material stayed for 3s, the powder was settled in the collection bottle, and the polymer microspheres were obtained after cooling;
[0041] S2. The polymer microspheres obtained in S1 are placed in deionized water, etched, stirred at a constant speed for 6 hours to remove PVP, centrifuged, washed with deionized water for 3-5 times, and dried to obtain the etched PMMA microspheres with an average particle size of 100-300 nm.
[0042] 10 parts by mass of the etched PMMA microspheres prepared above, 2 parts by mass of dispersant polyvinyl pyrrolidone, and 7 parts by mass of adhesive epoxy resin were added to an appropriate amount of deionized water, and dispersed at a stirring speed of 1000 rpm for 30 minutes. The resulting mixed solution was placed in a ball mill and ball milled at 600 rpm for 1 hour to prepare a mixture slurry; the mixture slurry was coated on both sides of a 10 μm PET base film to form a PMMA microsphere coating with a single-side thickness of 4 μm, and then placed in an oven at 60°C for drying to obtain the PMMA microsphere lithium-ion battery separator.
[0043] Embodiment 4: A method for preparing a PMMA microsphere lithium ion battery separator, comprising the following steps:
[0044] S1. 1 part by mass of PMMA and 2 parts by mass of PVP were mixed, melt-blended at 130°C, atomized and granulated at 100°C, the spray chamber gradient temperature was set to 100°C, the atomization pressure was 0.5MPa, a plurality of atomizing nozzles were provided on the atomizing disk, the inner diameter of the nozzle was 0.5mm, the peristaltic pump feed rate was 1L / h, the air volume was 72CFM, the material stayed for 3s, the powder was settled in a collection bottle, and the polymer microspheres were obtained after cooling;
[0045] S2. The polymer microspheres obtained in S1 are placed in deionized water, etched, stirred at a constant speed for 8 hours to remove PVP, centrifuged, washed with deionized water for 3-5 times, and dried to obtain the etched PMMA microspheres with an average particle size of 100-300 nm.
[0046] 10 parts by mass of the etched PMMA microspheres prepared above, 2 parts by mass of dispersant polyacrylamide, and 7 parts by mass of adhesive polyurethane were added to an appropriate amount of deionized water, and dispersed at a stirring speed of 1000 rpm for 30 minutes. The resulting mixed solution was placed in a ball mill and ball milled at 600 rpm for 1 hour to prepare a mixture slurry; the mixture slurry was coated on both sides of a 10 μm PE base film to form a PMMA microsphere coating with a single-side thickness of 2 μm, and then placed in an oven at 60°C for drying to obtain the PMMA microsphere lithium-ion battery separator.
[0047] Comparative Example 1: A method for preparing a PMMA microsphere lithium ion battery separator, comprising the following steps:
[0048] S1. 1 part by mass of PMMA was melted at 130°C, atomized and granulated at 100°C, the spray chamber gradient temperature was set to 100°C, the atomization pressure was 0.5MPa, a plurality of atomizing nozzles were provided on the atomizing disk, the inner diameter of the nozzle was 0.5mm, the peristaltic pump feed rate was 1L / h, the air volume was 72CFM, the material was retained for 3s, the powder was settled in a collection bottle, and the polymer microspheres were obtained after cooling;
[0049] S2. Place the polymer microspheres obtained in S1 in deionized water, stir at a constant speed for 7 hours, wash with deionized water for 3-5 times, and dry to obtain PMMA microspheres with an average particle size of 100-300 nm.
[0050] 10 parts by mass of the PMMA microspheres prepared above, 2 parts by mass of dispersant polyvinyl alcohol, and 7 parts by mass of adhesive polymethyl methacrylate were added to an appropriate amount of deionized water, and dispersed at a stirring speed of 1000 rpm for 30 minutes. The resulting mixed solution was placed in a ball mill and ball milled at 600 rpm for 1 hour to prepare a mixture slurry; the mixture slurry was coated on both sides of a 10 μm PE base film to form a PMMA microsphere coating with a single-side thickness of 3 μm, and then placed in an oven for drying at 60°C to obtain the PMMA microsphere lithium-ion battery separator.
[0051] Compared with Example 1, the PMMA microspheres in this comparative example were not subjected to etching treatment.
[0052] Comparative Example 2: A method for preparing a PMMA microsphere lithium-ion battery separator, comprising the following steps:
[0053] S1. 1 part by mass of PMMA and 3 parts by mass of PVP were mixed, melt-blended at 120°C, atomized and granulated at 100°C, the spray chamber gradient temperature was set to 100°C, the atomization pressure was 0.5MPa, a plurality of atomizing nozzles were provided on the atomizing disk, the nozzle inner diameter was 0.5mm, the peristaltic pump feed rate was 1L / h, the air volume was 72CFM, the material stayed for 3s, the powder was settled in a collection bottle, and the polymer microspheres were obtained after cooling;
[0054] S2. The polymer microspheres obtained in S1 are placed in deionized water, etched, stirred at a constant speed for 7 hours to remove PVP, centrifuged, washed with deionized water for 3-5 times, and dried to obtain the etched PMMA microspheres with an average particle size of 100-300 nm.
[0055] 10 parts by mass of the etched PMMA microspheres prepared above, 2 parts by mass of dispersant polyvinyl alcohol, and 7 parts by mass of adhesive polymethyl methacrylate were added to an appropriate amount of deionized water, and dispersed at a stirring speed of 1000 rpm for 30 minutes. The resulting mixed solution was placed in a ball mill and ball milled at 600 rpm for 1 hour to prepare a mixture slurry; the mixture slurry was coated on both sides of a 10 μm PE base film to form a PMMA microsphere coating with a single-side thickness of 3 μm, and then placed in an oven at 60°C for drying to obtain the PMMA microsphere lithium-ion battery separator.
[0056] Compared with Example 1, the melt blending temperature in step S1 of this comparative example is too low.
[0057] Comparative Example 3: A method for preparing a PMMA microsphere lithium ion battery separator, comprising the following steps:
[0058] S1. 1 part by mass of PMMA and 3 parts by mass of PVP were mixed, melt-blended at 150°C, atomized and granulated at 100°C, the spray chamber gradient temperature was set to 100°C, the atomization pressure was 0.5MPa, a plurality of atomizing nozzles were provided on the atomizing disk, the inner diameter of the nozzle was 0.5mm, the peristaltic pump feed rate was 1L / h, the air volume was 72CFM, the material stayed for 3s, the powder was settled in a collection bottle, and the polymer microspheres were obtained after cooling;
[0059] S2. The polymer microspheres obtained in S1 are placed in deionized water, etched, stirred at a constant speed for 7 hours to remove PVP, centrifuged, washed with deionized water for 3-5 times, and dried to obtain the etched PMMA microspheres with an average particle size of 100-300 nm.
[0060] 10 parts by mass of the etched PMMA microspheres prepared above, 2 parts by mass of dispersant polyvinyl alcohol, and 7 parts by mass of adhesive polymethyl methacrylate were added to an appropriate amount of deionized water, and dispersed at a stirring speed of 1000 rpm for 30 minutes. The resulting mixed solution was placed in a ball mill and ball milled at 600 rpm for 1 hour to prepare a mixture slurry; the mixture slurry was coated on both sides of a 10 μm PE base film to form a PMMA microsphere coating with a single-side thickness of 3 μm, and then placed in an oven at 60°C for drying to obtain the PMMA microsphere lithium-ion battery separator.
[0061] Compared with Example 1, the melt blending temperature in step S1 of this comparative example is too high.
[0062] Comparative Example 4: A method for preparing a PMMA microsphere lithium ion battery separator, comprising the following steps:
[0063] S1. 1 part by mass of PMMA and 3 parts by mass of PVP were mixed, melt-blended at 130°C, atomized and granulated at 70°C, the spray chamber gradient temperature was set to 70°C, the atomization pressure was 0.5MPa, a plurality of atomizing nozzles were provided on the atomizing disk, the nozzle inner diameter was 0.5mm, the peristaltic pump feed rate was 1L / h, the air volume was 72CFM, the material stayed for 3s, the powder was settled in the collection bottle, and the polymer microspheres were obtained after cooling;
[0064] S2. The polymer microspheres obtained in S1 are placed in deionized water, etched, stirred at a constant speed for 7 hours to remove PVP, centrifuged, washed with deionized water for 3-5 times, and dried to obtain the etched PMMA microspheres with an average particle size of 100-300 nm.
[0065] 10 parts by mass of the etched PMMA microspheres prepared above, 2 parts by mass of dispersant polyvinyl alcohol, and 7 parts by mass of adhesive polymethyl methacrylate were added to an appropriate amount of deionized water, and dispersed at a stirring speed of 1000 rpm for 30 minutes. The resulting mixed solution was placed in a ball mill and ball milled at 600 rpm for 1 hour to prepare a mixture slurry; the mixture slurry was coated on both sides of a 10 μm PE base film to form a PMMA microsphere coating with a single-side thickness of 3 μm, and then placed in an oven at 60°C for drying to obtain the PMMA microsphere lithium-ion battery separator.
[0066] Compared with Example 1, the atomization granulation temperature in step S1 of this comparative example is too low.
[0067] Comparative Example 5: A method for preparing a PMMA microsphere lithium ion battery separator, comprising the following steps:
[0068] S1. 1 part by mass of PMMA and 3 parts by mass of PVP were mixed, melt-blended at 130°C, atomized and granulated at 130°C, the spray chamber gradient temperature was set to 130°C, the atomization pressure was 0.5MPa, a plurality of atomizing nozzles were provided on the atomizing disk, the nozzle inner diameter was 0.5mm, the peristaltic pump feed rate was 1L / h, the air volume was 72CFM, the material stayed for 3s, the powder was settled in the collection bottle, and the polymer microspheres were obtained after cooling;
[0069] S2. The polymer microspheres obtained in S1 are placed in deionized water, etched, stirred at a constant speed for 7 hours to remove PVP, centrifuged, washed with deionized water for 3-5 times, and dried to obtain the etched PMMA microspheres with an average particle size of 100-300 nm.
[0070] 10 parts by mass of the etched PMMA microspheres prepared above, 2 parts by mass of dispersant polyvinyl alcohol, and 7 parts by mass of adhesive polymethyl methacrylate were added to an appropriate amount of deionized water, and dispersed at a stirring speed of 1000 rpm for 30 minutes. The resulting mixed solution was placed in a ball mill and ball milled at 600 rpm for 1 hour to prepare a mixture slurry; the mixture slurry was coated on both sides of a 10 μm PE base film to form a PMMA microsphere coating with a single-side thickness of 3 μm, and then placed in an oven at 60°C for drying to obtain the PMMA microsphere lithium-ion battery separator.
[0071] Compared with Example 1, the atomization granulation temperature in step S1 of this comparative example is too high.
[0072] The etched PMMA microspheres in the PMMA microsphere lithium ion battery separator of Example 1 were characterized and analyzed, and the results are as follows:
[0073] The microstructure of the etched PMMA microspheres obtained in this embodiment is shown in FIG. Figure 1 As shown. Figure 1 It can be seen that the etched PMMA microspheres obtained in this embodiment have obvious pore structures, high porosity, relatively good sphericity, relatively uniform particle sizes of about 100-300 nm, no obvious agglomeration, and good dispersibility.
[0074] The test results of the other embodiments are basically consistent with it.
[0075] The performance tests of Examples 1-4 and Comparative Examples 1-5 were performed, and the specific test methods are as follows:
[0076] Bonding strength: The positive electrode sheet and the separator were hot pressed at 80°C and 0.5MPa for 30s. After being cut into strips, a 180° peel strength test was performed on a universal tensile testing machine. The data obtained is the bonding strength of the separator.
[0077] Ionic conductivity: Test on an electrochemical workstation, record data and calculate ionic conductivity.
[0078] The results are shown in the following table:
[0079]
[0080] Electrochemical performance test: The PMMA microsphere lithium-ion battery separator was assembled into a battery and subjected to constant current charge and discharge cycle test at 1C and 5C currents to measure and calculate its electrochemical performance.
[0081] The results are shown in the following table:
[0082]
[0083] It can be seen from Tables 1 and 2 above that the PMMA microsphere lithium ion battery separators prepared in the embodiments of the present invention have excellent bonding strength and ionic conductivity, and the battery using the PMMA microsphere lithium ion battery separator has high charge and discharge specific capacity and excellent cycle stability.
[0084] In Comparative Example 1, since the PMMA microspheres have not been etched, the porosity is low, and the bonding strength and ion conductivity are low; in Comparative Example 2, the melt blending temperature is too low, and PVP fails to fully mix with PMMA, resulting in low internal porosity, low bonding strength and ion conductivity of the etched PMMA microspheres, and the battery charge and discharge specific capacity and cycle stability of the PMMA microsphere lithium-ion battery separator using the PMMA microspheres are average; in Comparative Example 3, the melt blending temperature is too high, and PVP undergoes a self-crosslinking reaction at high temperature and is converted into insoluble cross-linked PVP, resulting in the subsequent etching of PMMA microspheres. The actual low porosity, low bonding strength and ion conductivity, the battery charge and discharge specific capacity and cycle stability of the PMMA microsphere lithium-ion battery separator are poor; in Comparative Example 4, the atomization granulation temperature is too low, resulting in a larger particle size and low bonding strength of the etched PMMA microspheres; and in Comparative Example 5, the atomization granulation temperature is too high, the etched PMMA microspheres have a small particle size, and the particles are easily broken, and the battery cycle stability of the PMMA microsphere lithium-ion battery separator using the PMMA microspheres is poor.
[0085] In summary, the present invention prepares a PMMA microsphere lithium ion battery separator by compounding a base film, and a PMMA microsphere coating including etched PMMA microspheres, a dispersant, and an adhesive. The PMMA microspheres are subjected to a series of treatments such as melt blending, atomization granulation, and etching treatment to obtain nano-sized large-porosity etched PMMA microspheres, which effectively reduce the mass and thickness of the lithium ion battery separator, provide a better circulation and liquid retention channel for the electrolyte, improve the wettability of the separator and the electrolyte, and improve its ion conductivity, thereby improving the charge and discharge performance of the lithium ion battery. At the same time, the bonding strength is high and it is not easy to fall off, and the lithium ion conduction efficiency can be improved. The battery using the PMMA microsphere lithium ion battery separator has a high charge and discharge specific capacity and excellent cycle stability. The preparation method of the PMMA microsphere lithium ion battery separator is simple and easy to operate, the raw material source is wide, the production cost is low, and there is no pollution to the environment, and it has good economic and environmental benefits.
[0086] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solutions of the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A PMMA microsphere lithium ion battery separator, comprising: A base film, and a PMMA microsphere coating disposed on at least one side of the base film, wherein the PMMA microsphere coating at least comprises etched PMMA microspheres, a dispersant, and an adhesive, characterized in that: The etched PMMA microspheres are prepared by the following preparation method: S1. PMMA and PVP are mixed, melt-blended at 130-140°C, and atomized and granulated at 80-120°C to obtain polymer microspheres; S2. The polymer microspheres obtained in S1 are placed in deionized water, etched, centrifuged, washed with deionized water for 3-5 times, and dried to obtain the etched PMMA microspheres.
2. A PMMA microsphere lithium ion battery separator according to claim 1, characterized in that: The mass ratio of PMMA to PVP in S1 is 1:(1-3).
3. A PMMA microsphere lithium ion battery separator according to claim 1, characterized in that: S2 The etching treatment is to remove PVP by stirring at a constant speed for 6-8 hours.
4. A PMMA microsphere lithium ion battery separator according to claim 1, characterized in that: The average particle size of the etched PMMA microspheres is 100-300 nm.
5. A PMMA microsphere lithium ion battery separator according to claim 1, characterized in that: The single-side thickness of the PMMA microsphere coating is 2-5 μm.
6. A PMMA microsphere lithium ion battery separator according to claim 1, characterized in that: The base film material is one or more of PE, PP, PI, PEI, and PET.
7. A PMMA microsphere lithium ion battery separator according to claim 1, characterized in that: The base film has a thickness of 5-15 μm.
8. A PMMA microsphere lithium ion battery separator according to claim 1, characterized in that: The dispersant is one or more of polyvinyl alcohol, carboxymethyl cellulose and its salt, polyvinyl pyrrolidone and polyacrylamide.
9. A PMMA microsphere lithium ion battery separator according to claim 1, characterized in that: The adhesive is one or more of polymethacrylic acid, polymethyl methacrylate, styrene-butadiene rubber, polyurethane, and epoxy resin.
10. A lithium ion battery, characterized in that: The invention comprises a positive electrode, a negative electrode, an electrolyte located between the positive electrode and the negative electrode, and a PMMA microsphere lithium ion battery separator according to any one of claims 1 to 9.
Citation Information
Patent Citations
Coated diaphragm and preparation method thereof
CN114361706A
Preparation method of high-temperature-resistant PVDF battery diaphragm material
CN111730884A
High-performance lithium ion battery diaphragm and preparation method thereof
CN112952289A